Maternal‐to‐fetal allopurinol transfer and xanthine oxidase suppression in the late gestation pregnant rat. Issue 6 (13th November 2013) - Kane, Andrew D.; Camm, Emily J.; Richter, Hans G.; Lusby, Ciara; Tijsseling, Deodata; Kaandorp, Joepe J.; Derks, Jan B.; Ozanne, Susan E.; Giussani, Dino A.
Abstract: Fetal brain hypoxic injury remains a concern in high‐risk delivery. There is significant clinical interest in agents that may diminish neuronal damage during birth asphyxia, such as in allopurinol, an inhibitor of the prooxidant enzyme xanthine oxidase. Here, we established in a rodent model the capacity of allopurinol to be taken up by the mother, cross the placenta, rise to therapeutic levels, and suppress xanthine oxidase activity in the fetus. On day 20 of pregnancy, Wistar dams were given 30 or 100 mg kg −1 allopurinol orally. Maternal and fetal plasma allopurinol and oxypurinol concentrations were measured, and xanthine oxidase activity in the placenta and maternal and fetal tissues determined. There were significant strong positive correlations between maternal and fetal plasma allopurinol ( r  = 0.97, P  < 0.05) and oxypurinol ( r  = 0.88, P  < 0.05) levels. Under baseline conditions, maternal heart (2.18 ± 0.62 mU mg −1 ), maternal liver (0.29 ± 0.08 mU mg −1 ), placenta (1.36 ± 0.42 mU mg −1 ), fetal heart (1.64 ± 0.59 mU mg −1 ), and fetal liver (0.14 ± 0.08 mU mg −1 ) samples all showed significant xanthine oxidase activity. This activity was suppressed in all tissues 2 h after allopurinol administration and remained suppressed 24 h later ( P  < 0.05), despite allopurinol and oxypurinol levels returning toward baseline. The data establish a mammalian model of xanthine oxidase inhibition in the mother, placenta, and fetus, allowing investigation of the role of xanthine oxidase–derived reactive oxygen species in the maternal, placental, and fetal physiology during healthy and complicated pregnancy. Abstract : e00156 No small animal model of allopurinol administration to the mother during pregnancy has been established. Such a model is indispensable in species with a comparatively shorter life span to allow follow up of the effects of xanthine oxidase inhibition during pregnancy on the physiology of the offspring in later life. This study provides the capacity to investigate the long‐term consequences of maternal treatment with allopurinol on the physiology of the offspring, and to help establish the lasting safety of xanthine oxidase inhibition in human high‐risk pregnancy in current clinical obstetric practice.